Kajian terhadap Dinas Kebudayaan dan Pariwisata Kabupaten Blitar dalam Meningkatkan Jumlah Pengunjung di Museum Penataran - Dara Miftahurrohmah; Novita Setyoningrum; Fandu Dyangga Pradeta (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study examines the Blitar Regency Culture and Tourism Office's policy to increase visitor numbers at the Penataran Museum and identifies the obstacles encountered in its implementation. The method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The research subjects included cultural staff from the relevant office, Penataran Museum staff, and museum visitors. The results indicate that the office has implemented a policy encompassing three main aspects: improving access and services, protecting and developing collections, and sustainable collection management. Participatory programs such as education, cultural competitions, and information publications are also implemented to attract visitors, especially the younger generation. However, the implementation of this policy still faces various obstacles, such as limited personnel, time management, lack of collaboration with surrounding tourist destinations, and suboptimal publication, especially through digital media.